The Indonesian Food Security Policy: Mapping of Traditional Markets in Central Kalimantan - Syahirul Alam, Mochamad Doddy Syahirul Alam; Rhama, Bhayu; Setiawan, Ferry; Utami Irwan, Andi Ilmi; Selvia, Fitriana (Indonesian Association for Public Administration, 2024)
Food Security Policy is currently one of the government's focuses in anticipating future food crises. Food security, price stability, and supply chain channels are three things that cannot be separated in formulating a major policy on food security. This research aims to analyze supply chain connectivity through the existence of traditional markets in Central Kalimantan Province and analyze how traditional market development and management policies can encourage food security in Central Kalimantan Province. The research gap in this research is the phenomenon of relatively rapid fluctuations in food commodity prices when there is a national issue of increasing the price of one or several food commodities (sembako). This research is classified as qualitative research with an exploratory approach. Data was collected through several techniques, namely structured interviews, observation, and documentation, as well as the use of the Geographic Information System (GIS) application in mapping traditional markets in the Palangka Raya City Agglomeration area. The qualitative data analysis technique uses the Miles and Huberman interactive model. Findings in the field show that the coordinates of the locations of traditional markets in Palangka Raya City, Pulang Pisau Regency, Kapuas Regency, Katingan Regency, and East Kotawaringin Regency have been identified. However, there is no information on the commodities traded and the origin of the supply of these commodities. So it cannot be depicted through a map of the food supply chain in the Palangka Raya City agglomeration area. Regarding traditional market development and management policies in supporting food security, it turns out that this is the scope of duties of several agencies including the Development Planning and Research Development Agency (Bappedalitbang), the Agriculture and Food Crops Service, the Industry, Trade and Cooperatives Service (Disperindagkop). This research concludes that the Regional Government in the Palangka Raya City Agglomeration area has relatively the same policies regarding food security but has different strategies adapted to the potential of their respective regions.